Systematic literature review on digital courseware usage in Geography subjects for secondary school students - Nurulizzati Abdul Ghafar; Bahbibi Rahmatullah; Nor Asiah Razak; Fadhil Harfiez Abdul Muttallib; Muhamad Hariz Muhamad Adnan; Lia Laela Sarah (Pejabat Karang Mengarang UPSI, 2023)
Rapid technological advances are having an impact on the field of education. Multimedia courseware is a widely used option to help facilitate teaching and learning in the classroom. A large selection of courseware that covers many learning topics makes it easier for teachers to use it. The use of courseware that includes multimedia elements such as text, images, audio, and video, to some extent, can attract students and help their understanding process, in addition to its easy access on various platforms. However, little comprehensive analysis of digital courseware usage, especially in geography subjects for secondary school students. To the best of the authors' knowledge, no comprehensive analysis understands the use of digital courseware among students in geography subjects. Therefore, this systematic literature review aims to examine the use of courseware in the teaching and learning process of Geography subjects for secondary school students. The search strategy was made to gather articles in the Scopus databases from 2013 to 2021, and 257 articles have been found. Based on the inclusion and exclusion criteria, 13 articles were selected for the review. The findings of this systematic and comprehensive evaluation of the literature indicate that courseware can enhance learners' comprehension and encourage them to study Geography among students. The findings offer significant implications for digital courseware usage and geography subject communities, especially for policymakers, teachers, and developers to strategize and reflect on the practice they implemented and improvised if necessary for future sustainable education and efficient teachers' performance in teaching.